2022
DOI: 10.3390/ijms24010536
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Melanogenesis Effects of a Cyclic Peptide Derived from Flaxseed via Inhibition of CREB Pathway

Abstract: Linosorbs (Los) are cyclic peptides from flaxseed oil composed of the LO mixture (LOMIX). The activity of LO has been reported as being anti-cancer and anti-inflammatory. However, the study of skin protection has still not proceeded. In particular, there are poorly understood mechanisms of melanogenesis to LO. Therefore, we investigated the anti-melanogenesis effects of LOMIX and LO, and its activity was examined in mouse melanoma cell lines. The treatment of LOMIX (50 and 100 μg/mL) and LO (6.25–50 μM) suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Contrary to expectations, CLP-A and CLP-B only reduced the pigmentation in the cells without any cytotoxic effect on melanoma cells. The same effect was observed once CLP-A, CLP-B, CLP-D, CLP-E, CLP-F, and CLP-G were mixed [34]. A possible explanation for this effect may be a low concentration of the applied CLPs, as only concentrations of 25 to 100 µg/mL have been used [34].…”
Section: Melanoma and Clpsmentioning
confidence: 59%
See 4 more Smart Citations
“…Contrary to expectations, CLP-A and CLP-B only reduced the pigmentation in the cells without any cytotoxic effect on melanoma cells. The same effect was observed once CLP-A, CLP-B, CLP-D, CLP-E, CLP-F, and CLP-G were mixed [34]. A possible explanation for this effect may be a low concentration of the applied CLPs, as only concentrations of 25 to 100 µg/mL have been used [34].…”
Section: Melanoma and Clpsmentioning
confidence: 59%
“…The same effect was observed once CLP-A, CLP-B, CLP-D, CLP-E, CLP-F, and CLP-G were mixed [34]. A possible explanation for this effect may be a low concentration of the applied CLPs, as only concentrations of 25 to 100 µg/mL have been used [34]. Some experiments conducted in the past showed that cytotoxic effects would start at concentrations of at least 200 µg/mL.…”
Section: Melanoma and Clpsmentioning
confidence: 64%
See 3 more Smart Citations